Analisis Kinerja Keuangan Pemerintah Daerah Kabupaten Pamekasan Periode 2019 - 2021 - Nanda Ayu Septian; Dewianti Dwi Wahyuni; Sayekti Suindyah Dwiningwarni (Universitas Veteran Bangun Nusantara, 2023)
Analysis of the financial performance of the regional government of Pamekasan Regency in the period 2019 - 2021. Analysis of local government performance can be seen from the financial performance of an area. So to analyze the financial performance of a region by analyzing the financial ratios of the Regional Expenditure Budget (APBD) that have been set and have been implemented. This study aims to analyze the financial performance of the regional government of Pamekasan Regency in the period 2019 - 2021. The type of data used in this research is secondary data, so the type of research used in this research is descriptive quantitative using ratio analysis method. The results of the study show that the use of the regional government revenue budget for the Pamekasan district, seen from the analysis of the variance of the revenue budget for the 2019 - 2021 fiscal year based on the budget realization report, produces a positive balance value, meaning that the financial performance of local government revenues can be said to be good. So that the financial performance indicates that it has been able to obtain revenue in excess of the budgeted amount. The degree of decentralization that has occurred in Pamekasan district is relatively low so that financial dependence on the central government is relatively high. Meanwhile, in terms of the effectiveness ratio of PAD receipts in Pamekasan district, it can be concluded that during the 2019 - 2021 period it has been categorized as very effective because the PAD revenue target has exceeded the previous target.